2013
DOI: 10.5603/fm.2013.0016
|View full text |Cite
|
Sign up to set email alerts
|

Extra- and intracerebral course of the recurrent artery of Heubner

Abstract: Background:The aim of the current study was to analyse the extra-and intracerebral course of the recurrent artery of Heubner (RAH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
7
1
2
Order By: Relevance
“…The hypoplasia of the distal medial striated artery observed in our series was 43 cases (30.3%), it is considerably higher than previous reports and could be related to the decreased blood supply to the basal nuclei and anterior arm of the internal capsule, however, in these cases, it was found that the lenticulo-striated branches from the middle cerebral artery penetrated the anterior perforated substance and supplied the blood supply in this region 2 , 3 , 12 . In the event of an obstructive process of the proximal segment of the middle cerebral artery concomitantly with distal medial striated artery hypoplasia, the involvement of the regions irrigated by the latter is evident 2 , 3 , 13 .…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The hypoplasia of the distal medial striated artery observed in our series was 43 cases (30.3%), it is considerably higher than previous reports and could be related to the decreased blood supply to the basal nuclei and anterior arm of the internal capsule, however, in these cases, it was found that the lenticulo-striated branches from the middle cerebral artery penetrated the anterior perforated substance and supplied the blood supply in this region 2 , 3 , 12 . In the event of an obstructive process of the proximal segment of the middle cerebral artery concomitantly with distal medial striated artery hypoplasia, the involvement of the regions irrigated by the latter is evident 2 , 3 , 13 .…”
Section: Discussioncontrasting
confidence: 76%
“…La hipoplasia de la arteria estriada medial distal observada en nuestra serie fue de 43 casos (30.3%), es considerablemente más alta que los reportes anteriores y podría estar relacionada con una disminución del riego sanguíneo a los núcleos basales y al brazo anterior de la cápsula interna, sin embargo, en estos casos, se encontró que las ramas lenticuloestriadas de la arteria cerebral media penetraron en la sustancia perforada anterior y suministraron el riego sanguíneo en esta región 2 , 3 , 12 . En el caso de un proceso obstructivo del segmento proximal de la arteria cerebral media concomitantemente con hipoplasia de la arteria estriada medial distal, la afectación de las regiones irrigadas por esta última es evidente 2 , 3 , 13 .…”
Section: Discussionunclassified
“…Otros autores han llamado a este vaso, arteria central larga, arteria telencefálica, arteria estriada rostral y más recientemente arteria estriada medial distal (Maga et al, 2013a).…”
Section: Introductionunclassified
“…The anterior communicating artery complex consists of two anterior cerebral arteries (ACA), the anterior communicating artery (ACoA) and the recurrent arteries of Heubner [ 15 , 16 , 32 ]. ACA can be divided into the three following segments: A1 originating from the internal carotid artery, A2 extending from ACoA and A3 also known as the pericallosal artery [ 11 , 21 ].…”
Section: Introductionmentioning
confidence: 99%